Revoluce proti sob ě sam ým IV. sjezd Svazu československých spisovatelů 27.–29. června 1967, projevy a debaty v trojúhelníku spisovatelé, národ a moc - Vörös, István (Slavia Occidentalis, 2013)
1968 is a very controversial date these days. I start my research about 1968, by looking at 1967 first. Why? Because this congress was almost an exact projection of what happened during the Prague Spring, however, more was said there. The writers there were discussing the big questions, about a whole country and the destiny of a nation. Therefore, the importance of Kundera’s speech is quite significant. Havel, Vaculík, Ivan Klíma all gave politically important speeches. Regarding poetic power, Jan Skácel seemed especially strong. Even though Hrabal was not present, we have to give him some credit as well. Not only the positive, but also the negative side of 1968 was predicted. Mainly the Communist Party’s attempt to intervene. The Czech Spring of 1968 was not a student-movement, but a struggle by middle-aged and mature intellectuals, mostly against what they had instigated in their youth. So this was an exceptionally self-critical revolution.